Adaptation of an Obstetric Anesthesia Service for the Severe Acute Respiratory Syndrome Coronavirus-2 Pandemic: Description of Checklists, Workflows, and Development Tools. (January 2021) - Li, Yunping; Ciampa, Erin J.; Zucco, Liana; Levy, Nadav; Colella, Meredith; Golen, Toni; Shainker, Scott A.; Lunderberg, J. Mark; Ramachandran, Satya Krishna; Hess, Philip E.
Abstract : Background: Care of the pregnant patient during the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic presents many challenges, including creating parallel workflows for infected and noninfected patients, minimizing waste of materials, and ensuring that clinicians can seamlessly transition between types of anesthesia. The exponential community spread of disease limited the time for development and training. METHODS: The goals of our workflow and process development were to maximize safety for staff and patients, minimize the risk of contamination, and reduce the waste of unused supplies and materials. We used a cyclical improvement system and the plus/delta debriefing method to rapidly develop workflows consisting of sequential checklists and procedure-specific packs. RESULTS: We designed independent workflows for labor analgesia, neuraxial anesthesia for cesarean delivery, conversion of labor analgesia to cesarean anesthesia, and general anesthesia. In addition, we created procedure-specific material packs to optimize supplies and prevent wastage. Finally, we generated sequential checklists to allow staff to perform standard operating procedures without extensive training. CONCLUSIONS: Collectively, these workflows and tools allowed our staff to urgently care for patients in high-risk situations without prior experience. Over time, we refined the workflows using a cyclical improvement system. We present our checklists and workflows as well as the system we used for their development, so that others may use them to their benefit.